Adeno-Associated Viral Vector Serotype DJ-Mediated Overexpression of N171-82Q-Mutant Huntingtin in the Striatum of Juvenile Mice Is a New Model for Huntington’s Disease - Jang, Minhee; Lee, Seung Eun; Cho, Ik-Hyun (Frontiers in Cellular Neuroscience, 2018)
Huntington's disease (HD) is an autosomal-dominant inherited neurodegenerative disorder characterized by motor, psychiatric, and cognitive symptoms. HD is caused by an expansion of CAG repeats in the huntingtin (HTT) gene in various areas of the brain including striatum. There are few suitable animal models to study the pathogenesis of HD and validate therapeutic strategies. Recombinant adeno-associated viral (AAV) vectors successfully transfer foreign genes to the brain of adult mammalians. In this article, we report a novel mouse model of HD generated by bilateral intrastriatal injection of AAV vector serotype DJ (AAV-DJ) containing N171-82Q mutant HTT (82Q) and N171-18Q wild type HTT (18Q; sham). The AAV-DJ-82Q model displayed motor dysfunctions in pole and rotarod tests beginning 4 weeks after viral infection in juvenile mice (8 weeks after birth). They showed behaviors reflecting neurodegeneration. They also showed increased apoptosis, robust glial activation, and upregulated representative inflammatory cytokines (tumor necrosis factor-alpha and interleukin-6), mediators (cyclooxygenase-2 and inducible nitric oxide synthase) and signaling pathways (nuclear factor kappa B and signal transducer and activator of transcription 3) in the striatum at 10 weeks after viral infection (14 weeks after birth) via successful transfection of mutant HTT into neurons, microglia, and astrocytes in the striatum. However, little evidence of any of these events was found in mice infected with the AAV-DJ-18Q expressing construct. Intrastriatal injection of AAV-DJ-82Q might be useful as a novel in vivo model to investigate the biology of truncated N-terminal fragment (N171) in the striatum and to explore the efficacy of therapeutic strategies for HD.